Fabrication and in vitro investigation of nanohydroxyapatite, chitosan, poly(L‐lactic acid) ternary biocomposite. Issue 3 (11th May 2012) - Zhang, C. Y.; Zhang, C. L.; Wang, J. F.; Lu, C. H.; Zhuang, Z.; Wang, X. P.; Fang, Q. F.
Abstract The nanohydroxyapatite/chitosan/poly(L‐lactic acid) (HA/CS/PLLA) ternary biocomposites were prepared by blending the hydroxyapatite/chitosan (HA/CS) nanocomposites with poly(L‐lactic acid) (PLLA) solution. Surface modification by grafting D‐, L‐lactic acid onto the HA/CS nanocomposites was designed to improve the bonding with PLLA. The FTIR and 13C‐NMR spectrum confirmed that the oligo(lactic acid) was successfully grafted onto the HA/CS nanocomposites, and the time‐dependent phase monitoring showed that the grafted copolymers were stable. The TEM morphology of the HA/CS/PLLA ternary nanocomposites showed that nano‐HA fibers were distributed homogeneously, compacted closely and wrapped tightly by the CS and PLLA matrix. The ternary biocomposites with the HA content of 60 and 67 wt % exhibited high compressive strength of about 160 MPa and suitable hydrophilicity. The in vitro tests exhibited that the ternary biocomposites have good biodegradability and bioactivity when immersed in SBF solutions. All the results suggested that the n‐HA/CS/PLLA ternary biocomposites are appropriate to application as bone substitute in bone tissue engineering. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013